2008
DOI: 10.1016/j.euroneuro.2007.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide-antinociception is mediated by opioid receptors and nitric oxide in the periaqueductal gray region of the midbrain

Abstract: Previous studies have shown that nitrous oxide (N 2 O)-induced antinociception is sensitive to antagonism by blockade of opioid receptors and also by inhibition of nitric oxide (NO) production. The present study was conducted to determine whether these occur within the same brain site. Mice were stereotaxically implanted with microinjection cannulae in the periaqueductal gray (PAG) area of the midbrain. In saline-pretreated mice, exposure to 70% N 2 O resulted in a concentrationdependent antinociceptive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Other studies in the literature have shown that higher doses of nitrous oxide are also effective in producing analgesia (29)(30)(31). Some have reported that 70% nitrous oxide showed a statistically significant improvement in pain scores.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies in the literature have shown that higher doses of nitrous oxide are also effective in producing analgesia (29)(30)(31). Some have reported that 70% nitrous oxide showed a statistically significant improvement in pain scores.…”
Section: Discussionmentioning
confidence: 94%
“…Antinociceptive responsiveness was assessed using the abdominal constriction test as previously described8. At varying time intervals following HBO 2 treatment, different groups of mice were treated i.p.…”
Section: Methodsmentioning
confidence: 99%
“…The underlying mechanisms of the analgesic action of N 2 O have been extensively investigated, but many aspects of the mechanism remain unclear. Since 1976 [1], there have been several reports describing the opioidergic mechanism of N 2 O-induced analgesia [2][3][4], but the opioid receptors and endogenous opioid peptides that are involved have not been clarified. We have previously shown that an absence of l-opioid receptors (MOP) in mice does not affect the analgesic effect of N 2 O or the antagonistic effect of naloxone on N 2 O-induced analgesia [5].…”
mentioning
confidence: 99%